Pendampingan Kelas Bahasa Berbasis Mobile-Assisted Language Learning Pada Mahasiswa Yalimo di Universitas Megarezky - Hasnani Hasnani (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Proficiency in Indonesian language is a key foundation for regional students adapting to the academic climate at university. Megarezky University, in collaboration with the South Sulawesi Provincial Language Center, has initiated a language enrichment program for students from Yalimo. However, an evaluation of the implementation showed that the conventional (face-to-face) program experienced sustainability challenges and was discontinued after several meetings due to technical and time constraints. This activity aims to provide a solution in the form of mobile-assisted language learning as a flexible, inclusive, and sustainable learning alternative. The implementation method includes a preparation stage, training on the use of digital learning applications, intensive mentoring via smartphone, and regular evaluations. The results of the activity indicate that the use of mobile phones successfully overcomes limitations of space and time, increases the active involvement of Yalimo students from various study programs (Midwifery, Nursing, Nutrition, Pharmacy, and Medical Laboratory Technology), and increases self-confidence in speaking, reading, and academic writing skills.